2019
DOI: 10.1177/0022427818819696
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Reality Scenario Method: Moving from Imagination to Immersion in Criminal Decision-making Research

Abstract: Objectives: This study proposes an alternative hypothetical scenario method capitalizing on the potential of virtual reality (VR). Rather than asking participants to imagine themselves in a specific situation, VR perceptually immerses them in it. We hypothesized that experiencing a scenario in VR would increase feelings of being "present" in the situation, and add to perceived realism compared to the written equivalent. This, in turn, was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 52 publications
5
46
0
Order By: Relevance
“…Our findings confirm that participants felt strong levels of both presence and involvement in the virtual environment. This mirrors findings in which individuals exposed to a 'bar-fight' in virtual reality reported higher feelings of presence and emotional responses (intention to aggress) than those reading a narrative of the same scene [75]. Both presence and emotion are important ingredients to forming an episodic memory [76]; the key variable of interest in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…Our findings confirm that participants felt strong levels of both presence and involvement in the virtual environment. This mirrors findings in which individuals exposed to a 'bar-fight' in virtual reality reported higher feelings of presence and emotional responses (intention to aggress) than those reading a narrative of the same scene [75]. Both presence and emotion are important ingredients to forming an episodic memory [76]; the key variable of interest in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…Rather than asking students to imagine themselves in a specific situation, VR perceptually immerses them in an experience, consequently triggering their imagination [37]. This study confirmed these findings with students acknowledging the iVR storytelling experience elicited their imaginations in believing they were inside a womb.…”
Section: Discussionsupporting
confidence: 75%
“…Moving forward, the use of virtual reality may be a strong alternative to written scenarios. Rather than asking participants to imagine themselves in a specific situation, virtual reality immerses them in it (van Gelder, de Vries, Demetriou, van Sintemaartensdijk, & Donker, ). Indeed, van Gelder and various coauthors (van Gelder et al., ; van Gelder et al., ) have demonstrated that “experiencing a scenario in virtual reality can trigger stronger feelings of presence in the situation compared to its written equivalent, and also elicit more intense emotional experiences, resulting in a better approximation of real‐world decision‐making” (, p. 469).…”
Section: Resultsmentioning
confidence: 99%
“…Rather than asking participants to imagine themselves in a specific situation, virtual reality immerses them in it (van Gelder, de Vries, Demetriou, van Sintemaartensdijk, & Donker, ). Indeed, van Gelder and various coauthors (van Gelder et al., ; van Gelder et al., ) have demonstrated that “experiencing a scenario in virtual reality can trigger stronger feelings of presence in the situation compared to its written equivalent, and also elicit more intense emotional experiences, resulting in a better approximation of real‐world decision‐making” (, p. 469). Furthermore, researchers could use more sophisticated techniques to capture the experience of emotions that are not sensitive to perceptual biases (e.g., heart rate monitors; Armstrong & Boutwell, ).…”
Section: Resultsmentioning
confidence: 99%